2015
DOI: 10.1111/mcn.12173
|View full text |Cite
|
Sign up to set email alerts
|

Adding multiple micronutrient powders to a homestead food production programme yields marginally significant benefit on anaemia reduction among young children inNepal

Abstract: Anaemia affects 46% of preschool-aged children in Nepal. A cluster-randomised study was conducted in rural Nepal to test whether providing micronutrient powders (MNP) in addition to enhanced homestead food production (EHFP) programme, consisting of home gardens, poultry and nutrition education, could lead to a higher reduction in anaemia compared with providing only EHFP. This sub-study enrolled 335 children aged 6-9 months into one of three groups: (1) EHFP + MNP; (2) EHFP; or (3) control. The EHFP + MNP grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 17 publications
2
33
1
Order By: Relevance
“…Recall bias due to underreporting and overreporting of morbidity events, has been shown in morbidity studies using recalled symptoms (Feikin et al, 2010). Our results are in line with the findings of reviews of oral iron supplementation trials that did not show an increased risk of malaria parasitemia (Pasricha, Hayes, Kalumba, & Biggs, 2013) and clinical malaria (Neuberger, Okebe, Yahav, & Paul, 2016) when regular malaria prevention or management services are provided.…”
Section: Morbiditysupporting
confidence: 89%
See 1 more Smart Citation
“…Recall bias due to underreporting and overreporting of morbidity events, has been shown in morbidity studies using recalled symptoms (Feikin et al, 2010). Our results are in line with the findings of reviews of oral iron supplementation trials that did not show an increased risk of malaria parasitemia (Pasricha, Hayes, Kalumba, & Biggs, 2013) and clinical malaria (Neuberger, Okebe, Yahav, & Paul, 2016) when regular malaria prevention or management services are provided.…”
Section: Morbiditysupporting
confidence: 89%
“…We found no difference in stunting and wasting prevalence or mean LAZ and WLZ between children at baseline and the follow‐up surveys. Several studies with randomized controlled design, which combined home fortification of foods with MNP and nutritional counselling sessions, found similar results (Inayati et al, ; Osei et al, ; Suchdev et al, ; Yousafzai et al, ). The results of studies using only MNP as intervention are mixed.…”
Section: Discussionmentioning
confidence: 71%
“…Relatively fewer episodes of morbidity among the comparison children at younger age could be explained by the fact that the MAL-ED children were recruited as healthy newborns, so better immunity, hence fewer chances of infectious morbidities [30]. Moreover, continuous interaction with the mothers and the research staff from the rigorous data collection in MAL-ED cohort study might responsible for "Hawthrone effect" resulted in reduced morbidity episodes [16,21]. There are several limitations in this study.…”
Section: Discussionmentioning
confidence: 94%
“…The reduction in the prevalence of anemia in this study is in concordance with a recently completed study which compared 2 months of daily MNP supplementation with 3 months and 4 months of flexible MNP supplementation in children under the age of 24 months from Bangladesh [20] and observed significant reduction in the prevalence of anemia across all three intervention groups when compared to baseline prevalence. In a cluster randomized study at rural Nepal observed a significant improvement of hemoglobin status after providing MNP to children 6-9 months old over a period of 11 months in flexible doses [21]. Moreover, in a community-based randomized trial in Ghana, significant effect on reduction of anemia prevalence was observed from daily dosage of MNP for 6 months among children from 6 to 12 months of age [17].…”
Section: Discussionmentioning
confidence: 98%
“…Osei et al . () describe the use of the homestead food production programme as a delivery channel for MNP. While delivery was successful, anaemia levels did not decline much, which is likely related to the relatively low dose provided (10 sachets per month, i.e.…”
Section: Access and Distribution Under (Semi) Real‐life Circumstancesmentioning
confidence: 99%